2016
DOI: 10.1080/17441692.2016.1173717
|View full text |Cite
|
Sign up to set email alerts
|

Health expenditure and catastrophic spending among older adults living with HIV

Abstract: These findings suggest that although HIV-positive and HIV-negative older adults in South Africa are protected to some extent from CHE, inequalities still exist in access to and quality of care available at health-care services - which can inform South Africa's development of a national health insurance scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Regarding the hospitalization expenses of different age groups, our statistical analysis results showed that the hospitalization expenses of group over 60 y were higher than those in the group under 30 y. comorbidity [30]. The research of Negin found that the rates of chronic disease were higher among older adults compared with those aged 18-49 y.…”
Section: Influencing Factors Of Totalexp and Oopsmentioning
confidence: 71%
See 1 more Smart Citation
“…Regarding the hospitalization expenses of different age groups, our statistical analysis results showed that the hospitalization expenses of group over 60 y were higher than those in the group under 30 y. comorbidity [30]. The research of Negin found that the rates of chronic disease were higher among older adults compared with those aged 18-49 y.…”
Section: Influencing Factors Of Totalexp and Oopsmentioning
confidence: 71%
“…showed the results of ordered logistic regression analysis about Totalexp and OOPs. Taking the group under 30 as the reference, the partial regression coefficient of the age group over 60 was statistically significant, OR(Totalexp)=1.809, OR(OOPs)=0 30…”
mentioning
confidence: 97%
“…Once clinical symptoms occur, the treatment becomes more difficult and costly. Meanwhile, the elderly with AIDS are at the high risk of comorbidity [30]. The research of Negin found that the rates of chronic disease were higher among older adults compared with those aged 18-49 y.…”
Section: Discussionmentioning
confidence: 99%
“…Another important finding in this study is that older participants who are living with HIV were more likely to report a recent visit to a health-care facility compared with their HIV negative counterparts (MRC/UVRI, 2011). A recent study conducted in South Africa that looked at both private and public health facilities found that private outpatient health services were accessed more by people living with HIV compared with HIV negative respondents (Negin et al., 2016). Previous studies conducted in this population have shown that the majority of older persons living with HIV are enrolled in care, and the majority of these are receiving ART; Negin et al., 2013).…”
Section: Discussionmentioning
confidence: 99%